KEWENANGAN POLRI DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - Satriya Nugraha (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2019)
Eradicating corruption in Indonesia has become a pillar measuring the realization of the ideals of good reform of the State administration. In realizing this, the National Police as a law enforcer has become one of the institutions that have authority with the Attorney General's Office and the Corruption Eradication Commission is always maximal in combating corruptors in Indonesia. This study aims to understand the authority of the Indonesian National Police in the Eradication of Corruption Crimes. The method in this study uses a type of normative legal research that examines the laws and regulations governing the authority of the Indonesian National Police in the Eradication of Corruption Crimes. In this study, it is known that the Indonesian National Police has the authority to investigate corruption by always coordinating with the Prosecutor, namely the Public Prosecutor who accepts the results of the Police investigation.